Development of the Register Assembling Method for Inpatient Patient Data Integration at RSUD Lawang - Salsabila Syahda Maharani; Retno Dewi Prisusanti; Rizka Andika Sari (Universitas Widya Gama Mahakam Samarinda, 2024)
Background: A register is a notebook or list containing names, addresses and so on that are contained in a person’s identity. The inpatient assembling register activity at Lawang Hospital is still not carried out optimally, officers in the assembling until still record the register of medical record files manually by writing in the register book, this affects the accuracy of writing patient data from medical record files returning from the ward and efficiency when providing medical record files. Objectives: The purpose of this study is to improve the quality of patient data recording in register activities in the integrated assembling unit using an electronic system. Research Metodes: The research method uses qualitative descriptive with 1 respondent who has been interviewed directly and by direct observation. Results: The results of this study show an overview of the Google Form and spreadsheet designs that have been created and also show significant changes after the switch method using electronic systems. Conclusion: The development of the register assembling method for inpatient medical record files has brought positive changes in the efficiency of health information management at Lawang Hospital. This study shows that the application of innovative technology can make it easier for medical record officers to register patient files more efficiently. With the use of Google Forms which is integrated with the spreadsheet of patient data that is inputted, it is easier to read and faster to trace the existence of files that have been assembling. Keywords: Method; Register; Assembling